Fine Particulate Air Pollution and Hospital Emergency Room Visits for Respiratory Disease in Urban Areas in Beijing, China, in 2013 - Xu, Qin (PLoS One, 2016)
BACKGROUND: Heavy fine particulate matter (PM(2.5)) air pollution occurs frequently in China. However, epidemiological research on the association between short-term exposure to PM(2.5) pollution and respiratory disease morbidity is still limited. This study aimed to explore the association between PM(2.5) pollution and hospital emergency room visits (ERV) for total and cause-specific respiratory diseases in urban areas in Beijing. METHODS: Daily counts of respiratory ERV from Jan 1 to Dec 31, 2013, were obtained from ten general hospitals located in urban areas in Beijing. Concurrently, data on PM(2.5) were collected from the Beijing Environmental Protection Bureau, including 17 ambient air quality monitoring stations. A generalized-additive model was used to explore the respiratory effects of PM(2.5), after controlling for confounding variables. Subgroup analyses were also conducted by age and gender. RESULTS: A total of 92,464 respiratory emergency visits were recorded during the study period. The mean daily PM(2.5) concentration was 102.1±73.6 μg/m(3). Every 10 μg/m(3) increase in PM(2.5) concentration at lag(0) was associated with an increase in ERV, as follows: 0.23% for total respiratory disease (95% confidence interval [CI]: 0.11%-0.34%), 0.19% for upper respiratory tract infection (URTI) (95%CI: 0.04%-0.35%), 0.34% for lower respiratory tract infection (LRTI) (95%CI: 0.14%-0.53%) and 1.46% for acute exacerbation of chronic obstructive pulmonary disease (AECOPD) (95%CI: 0.13%-2.79%). The strongest association was identified between AECOPD and PM(2.5) concentration at lag(0-3) (3.15%, 95%CI: 1.39%-4.91%). The estimated effects were robust after adjusting for SO(2), O(3), CO and NO(2). Females and people 60 years of age and older demonstrated a higher risk of respiratory disease after PM(2.5) exposure. CONCLUSION: PM(2.5) was significantly associated with respiratory ERV, particularly for URTI, LRTI and AECOPD in Beijing. The susceptibility to PM(2.5) pollution varied by gender and age.